2019
DOI: 10.14814/phy2.14071
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac‐specific ablation of glutaredoxin 3 leads to cardiac hypertrophy and heart failure

Abstract: Growing evidence suggests that redox‐sensitive proteins including glutaredoxins (Grxs) can protect cardiac muscle cells from oxidative stress‐induced damage. Mammalian Grx3 has been shown to be critical in regulating cellular redox states. However, how Grx3 affects cardiac function by modulating reactive oxygen species ( ROS ) signaling remains unknown. In this study, we found that the expression of Grx3 in the heart is decreased during aging. To assess the physiological role of Grx3 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Among them, cardiovascular adaptation is a surprising association with rapid sequence evolution during transition from the water column to benthic colonization. Our results revealed that this process may involve not only a cardiac morphological reorganization resulting from selective pressure on cardiac morphogenesis genes ( popdc2 and irx4a ) 54 , 56 , but also cardiac functional remodeling resulting from selective pressure on genes associated with cardiac conducting efficiency ( tmem43 and popdc2 ) 52 , 54 and antioxidant capacities ( glrx1 and glrx3 ) 55 , 57 (Extended Data Fig. 3 , Supplementary Tables 90 – 97 and Supplementary Notes 20 , 21 and 23 ).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Among them, cardiovascular adaptation is a surprising association with rapid sequence evolution during transition from the water column to benthic colonization. Our results revealed that this process may involve not only a cardiac morphological reorganization resulting from selective pressure on cardiac morphogenesis genes ( popdc2 and irx4a ) 54 , 56 , but also cardiac functional remodeling resulting from selective pressure on genes associated with cardiac conducting efficiency ( tmem43 and popdc2 ) 52 , 54 and antioxidant capacities ( glrx1 and glrx3 ) 55 , 57 (Extended Data Fig. 3 , Supplementary Tables 90 – 97 and Supplementary Notes 20 , 21 and 23 ).…”
Section: Resultsmentioning
confidence: 81%
“… 56 ) and glrx 3 (ref. 57 ) in FLP) (Supplementary Tables 90 – 97 , Extended Data Fig. 3 and Supplementary Notes 20 and 21 ), possibly suggesting a similar remodeling of their visual, immune, respiratory and circulatory systems in benthic adaptation to seafloor colonization (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to Glrx, Glrx2 and Glrx3 have also been shown to play a role in cardiac hypertrophy. Deletion of Glrx2 in mice hearts results in cardiac hypertrophy and fibrosis as well as hypertension [61], while Glrx3 KO in mice results in cardiac hypertrophy and heart failure [63]. Glrx3 KO mice were found to have significant left ventricular hypertrophy compared to their WT counterparts at 12 months of age.…”
Section: Cardiac Hypertrophymentioning
confidence: 99%
“…Differential expression was observed in the developing mammary glands [14] and also in muscle cells following hydrogen peroxide treatment [8]. As regards to the current investigation, Grx3 expression was also found to decline in the heart during aging [12]. Here we wanted to determine the impact of HFD feeding on Grx3 expression in the heart.…”
Section: Grx3 Expression In the Heart Of Dio Micementioning
confidence: 81%